Der Öraefajökull und die Landschaft Öraefi Die Entwicklung einer isländischen Siedlung im Kampf gegen die Naturgewalten - Thorarinsson, Sigurdur (ERDKUNDE, 1959)
When studying the history of an Icelandic rural settlement through the ages it is often possible to begin at the very beginning when the first immigrants settled there during the period 870-930 A. D., and localize the oldest farms. So is the case with the history of the isolated rural settlement Öræfi, in ancient times called Herad or Litla herad, situated at the foot of Iceland’s biggest volcano, Öræfajökull. Chartularies and other contemporary records, together with place names and farm ruins, reveal that near the middle of the 14th century there were 6 churches and about 30 farms in Herad. But the settlement was entirely devastated by a rhyolitic and purely explosive initial eruption of Öræfajökull in June 1362. The destruction was caused partly by glacier bursts, but mainly by the enormous tephrafall, as proved by the author’s tephro chronological studies. When the settlement revived again it had got its present, significative name, Öræfi, which means waste land. The first census in Iceland, in 1703, shows the structure of Öræfi at that time. Characteristic for the settlement then and now is that he farms are situated in groups, and not isolated as usually in Iceland. The main reason for this is that glacier bursts from Öræfajökull (in 1362 and 1727) and numerous glacier bursts from Gnmsvotn, advance of glacier tongues and oscillations of glacier rivers have gradually curtailed the habitable land and brought the farms together on the grass covered spots left. Now the aeroplane has broken the isolation of Öræfi, but the biggest farm groups still preserve much of their oldfashioned and interesting characteristics.